(untitled) (Journal of Social Sciences Review, 2023)
A strong banking system is essential for driving economic growth and improving social welfare, particularly in developing nations such as Pakistan. This is because the banking sector serves as the backbone of the economy. Therefore, stability and performance in the banking system are paramount for sustained progress and prosperity. Pakistan’s banking system has undergone significant changes due to comprehensive reforms that were implemented following the 1990 financial crisis at the local level. As a result, the system has undergone a fundamental transformation. The primary objective of our study is to present novel findings on the current government of the country’s banking Sector. To evaluate the performance levels of banks in Pakistan, we conducted a non-parametric data envelopment analysis (DEA) that compared the performance of Islamic Vs. Traditional Banks. We calculated the shadow return on equity (SROE) by formulating a frontier cost function specification that is constrained by capitalization. Furthermore, we investigated the relationship between performance and shadow return on equity using a panel vector auto regression (PVAR) framework. Lastly, we examined the scale economies within the banking Sector in Pakistan, and our results have significant implications for regulatory decision-making and analysis.